G254(P) Incidence of firework related injuries at royal hospital children for glasgow. (25th October 2020) - Dobbin, J; Watson, S; Ramsay, S
Abstract : Aims and Objectives: Annual incidence of firework related injuries from 2015–2018. (Injuries included those sustained from fireworks, sparklers and bonfires.) To assess if incidence of firework related injuries is increasing. To assess relationship between firework injuries and SIMD index Methods: Data was collected from nurse led burns clinic attendees and A&E attendees between 31st October and 10th November from 2015–2018. The type of injury; site of injury; age when injured; gender; severity of burn; and postcode were collected. Postcode data was then inserted into Scottish Index of Multi Depravation Index (SIMD) database to extract SIMD index. Results: 30 children were injured by fireworks, sparklers or bonfire between 2015 and 2018, 9 females and 21 males. Ages ranged from 2–15 years. The most common body part injured was the hand (n=17) and the majority of injuries happened on bonfire night (n=16). Fireworks injured the most people (n=18), followed by sparklers (n=8) and then bonfires (n=4). The majority of injuries were superficial (n=15). Firework related injuries also seem to be on the increase, and this is depicted in table 1 below. Lower SIMD indices had higher indices of burns (p=0.0015) and this is depicted in table 2 . Conclusions: Firework related injuries increased by almost double in 2018 compared to 3 previous years. Lower SIMD quintile ranking also had significantly more firework related injuries. This could suggest a link between depravation and likelihood of firework injury. This information could be used to target more deprived areas with firework safety campaigns, as well as overall increase in campaigning in 2019 to assess if injuries can be reduced in 2019.